New strategies for managing dollar spot and silvery-thread moss in creeping bentgrass putting greens - Thompson, Cole S. (Kansas State University, 2011)
Dollar spot, caused by Sclerotinia homoeocarpa F.T. Bennett, and silvery-thread moss (Bryum argenteum Hedw.) are pests affecting creeping bentgrass (Agrostis stolonifera L.) that typically require pesticide inputs. New strategies for pest management may reduce chemical inputs. The objectives of these 2009-2010 field studies were to evaluate: 1) creeping bentgrass cultivars for dollar spot susceptibility; 2) alternative chemical controls for silvery-thread moss; and 3) the response of silvery-thread moss to nitrogen (N) sources. During peak dollar spot development, ‘Declaration’, ‘A-4’, and ‘Crenshaw’ had 7.5, 139.4, and 288.9 infection centers m[superscript]-2 under fairway and 2.1, 27.2, and 106.9 infection centers m[superscript]-2 under putting green conditions, respectively. Two spring and two fall spot applications of sodium or potassium bicarbonate (45 g a.i. L[superscript]-1), premixed essential oil, and broadcast applications of carfentrazone-ethyl at 0.09 kg a.i. ha[superscript]-1 suppressed moss 39% to 55% compared to untreated in 2009. Spot sprays of sodium or potassium bicarbonate, and essential oil, were phytotoxic to creeping bentgrass and required up to 8 or 18 days, respectively, to return to acceptable quality. Fertilization with liquid urea (N at 16.3 kg ha[superscript]-1 biweekly, 210 kg ha[superscript]-1 annually) resulted in 147%, 150%, and 155% more moss than fertilization with IBDU, organic N, and granular urea, respectively, and 156% more moss compared to untreated. Fertilization with urea (liquid or granular) resulted in the best creeping bentgrass color. Averaged across the entire season, plots treated with organic N had unacceptable color in 2009. Nitrogen concentrations in moss tissue ranged from 0.4% to 1.0% and were always significantly lower than N concentrations observed in creeping bentgrass (1.1% to 2.1%), regardless of treatment. In 2010, moss treated with liquid urea had higher tissue N concentrations (1.0%) than untreated moss (0.5%) or that fertilized with IBDU (0.4%). In summary, use of dollar spot-resistant creeping bentgrass cultivars could reduce fungicide requirements. Bicarbonate and essential oil products can reduce moss severity at a similar level to carfentrazone-ethyl, but rates and/or application methods need to be optimized to avoid injury to creeping bentgrass. Applications of liquid urea enhanced moss coverage in creeping bentgrass compared to other N sources.
Keywords: Susceptibility of creeping bentgrass cultivars to dollar spot; Alternative control of silvery-thread moss in creeping bentgrass putting greens; Horticulture (0471)